PELATIHAN PEMBUATAN SOSIS DENGAN PENAMBAHAN DAUN KELOR DI DESA BATULAYA, KECAMATAN TINAMBUNG, KABUPATEN POLEWALI MANDAR - Mukhlisah, Andi Nurul; Nuraliah, Siti; Dwi Ningtyas, Weny (Jurnal Pengabdian Masyarakat Polmanbabel, 2024)
Sausage is a food product obtained from a mixture of fine meat and flour or starch with the addition of seasonings, and food additives that are inserted into the sausage casing. In the preliminary experiment of making sausage, the product was unattractive, yellowish-white, thus making consumer interest decrease. Therefore, to add variants of sausages and increase the nutritional value of sausages, the addition of moringa leaves is one alternative that can be used. Moringa leaves or Moringa oleifera is one type of vegetable that is rich in macro and micronutrients. The implementation method to solve the problem is carried out with an institutional approach, which is a process of continuous guidance and mentoring during the activity. The participants involved in this activity were 60 people consisting of PKK mothers and youth groups in Batulaya Village. The implementation of this assistance is focused on guiding and assisting PKK mothers in terms of applying livestock product processing technology in the form of sausages. Community service activities by conducting counseling followed by training and mentoring for PKK mothers in Batulaya Village, Tinambung District, Polewali Mandar Regency were able to increase their knowledge and ability to make sausages with the addition of moringa. In general, the implementation of this activity provides information to PKK mothers that livestock products, especially sausages, can not only be processed into food ingredients but can also prevent stunting with the innovation of adding moringa leaves so that it becomes a business opportunity to increase the income of PKK members. During the activity, participants actively asked questions related to the process of making processed livestock products, especially the stages of making chicken meat sausage with the addition of moringa leaves, starting the process of grinding meat, mixing spices, inserting in the sleeve, steaming, and packaging.